2021
DOI: 10.1038/s41419-021-03781-x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium/glucose cotransporter 1-dependent metabolic alterations induce tamoxifen resistance in breast cancer by promoting macrophage M2 polarization

Abstract: Endocrine therapy is the standard treatment for estrogen receptor (ER)-positive breast cancer, but tumors eventually develop resistance. However, endocrine therapy resistance mechanisms mediated through interactions between breast cancer cells and tumor-associated macrophages (TAMs) are still unclear. Here, we characterized sodium/glucose cotransporter 1 (SGLT1) overexpression drives the highly glycolytic phenotype of tamoxifen-resistant breast cancer cells where enhanced lactic acid secretion promotes M2-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…For instance, Anders Etzerodt et al reported that CD163+ TAMs infiltration occurs in melanomas and is associated with the resistance of PD-1/PD-L1 therapy [ 68 ]. Studies indicated that nutrient deprivation in the TME impairs the functions of T cells or NK cells [ 69 ], and enforces macrophage polarization into TAMs through reprogramming their metabolic patterns [ 70 ]. Recent studies have shown that TAMs express elevated levels of the scavenger receptor CD36, accumulate lipid droplets, and utilize fatty acid oxidation (FAO) for energy generation to support tumor growth [ 71 ].…”
Section: Heterogeneous Tam Polarizationmentioning
confidence: 99%
“…For instance, Anders Etzerodt et al reported that CD163+ TAMs infiltration occurs in melanomas and is associated with the resistance of PD-1/PD-L1 therapy [ 68 ]. Studies indicated that nutrient deprivation in the TME impairs the functions of T cells or NK cells [ 69 ], and enforces macrophage polarization into TAMs through reprogramming their metabolic patterns [ 70 ]. Recent studies have shown that TAMs express elevated levels of the scavenger receptor CD36, accumulate lipid droplets, and utilize fatty acid oxidation (FAO) for energy generation to support tumor growth [ 71 ].…”
Section: Heterogeneous Tam Polarizationmentioning
confidence: 99%
“…Several components of TME, including hypoxia ( 41 ), cancer-associated fibroblasts ( 42 ), ECM ( 11 ), immune cells, and inflammatory cytokines such as IL-1β, transforming growth factor-β (TGF-β), and TNF-α ( 10 , 43 ) have been shown to be associated with endocrine resistance. Our team has also revealed some of the endocrine resistance mechanisms involving the immune microenvironment in previous studies such as that high SGLT1 expression mediates enhanced glucose uptake and lactic acid secretion, promoting M2-like tumor-associated macrophage (TAM) polarization and feedback activation of EGFR/PI3K/Akt/SGLT1 signaling in tumor cells to enhance tamoxifen resistance ( 44 ). Another article also proposed that TAMs increased the expression of cyclooxygenase-2 (COX-2)/prostaglandin E2 (PGE2), which promoted tamoxifen resistance ( 45 ).…”
Section: Discussionmentioning
confidence: 90%
“…The transporter increases glycolytic flux and lactate production via aerobic glycolysis which induces a tumor-associated macrophage. The macrophage then promotes cell growth via EGFR/PI3K/Akt signaling, releasing immunosuppressive factors [ 44 ]. In line with the previous study, there is other evidence suggesting that high expression of SGLT1 correlates to a high growth rate of TNBC [ 45 ].…”
Section: Mrs Targeting Glucose Metabolismmentioning
confidence: 99%